Study on the phase I metabolism of novel synthetic cannabinoids, APICA and its fluorinated analogue. Issue 2 (26th November 2014) - Sobolevsky, Tim; Prasolov, Ilya; Rodchenkov, Grigory
<x xml:space="preserve">Abstract</x> The data are reported for an in vitro metabolism study of two novel synthetic cannabinoids, N‐(1‐adamantyl)‐1‐pentyl‐1H‐indole‐3‐carboxamide (APICA) and its fluorinated analog N‐(1‐adamantyl)‐1‐(5‐fluoropentyl)‐1H‐indole‐3‐carboxamide (5F‐APICA, STS‐135), which are active ingredients of smoking mixtures sold in Russia since 2012. The cannabinoids were isolated from herbal mixtures using preparative liquid chromatography and then incubated with human liver microsomes (HLMs). The formed metabolites were characterized by liquid chromatography – triple quadrupole mass spectrometry and high‐resolution mass spectrometry with electrospray ionization in positive ion mode. It was found that HLMs produce mono‐, di‐, and trihydroxylated metabolites, as well as N‐desalkyl metabolites, which can be further hydroxylated; the amide bond resisted the metabolic cleavage. For 5F‐APICA, a series of oxidative defluorination products formed as well. For in vivo confirmation of the formed in vitro metabolites, spot urine samples from drug users were analyzed with the created method. It was shown that for the detection of APICA abuse, the preferred metabolites are the di‐ and tri‐hydroxylated species, while in case of 5F‐APICA, a monohydroxy metabolite is a better target. The N‐despentyl (desfluoropentyl) hydroxyadamantyl metabolite also provides good retrospectivity to confirm the administration of any of these cannabinoids. Copyright © 2014 John Wiley & Sons, Ltd.